The challenges of feedback in higher education. Issue 8 (17th November 2019) - Henderson, Michael; Ryan, Tracii; Phillips, Michael
Abstract: Assessment feedback is one of the most important components of the learning process. However, student and educator dissatisfaction with feedback practices continues to remain a significant problem in higher education. To better understand the barriers to effective feedback, the present study explores feedback challenges identified by 3807 students and 281 educators from two Australian universities. Open-response data were analysed using an inductively derived coding framework and thematic analysis. The findings reveal three major themes relating to the challenges of feedback from the perspective of students and educators: feedback practices, contextual constraints and individual capacity. In addition to confirming the persistence of many previously reported challenges in the literature, this paper also offers insights into challenges that are particular to feedback, especially relating to the production of useful comments and the perceived hurdles of both student and educator attitudes and capabilities. The findings also highlight the constrained nature of educators' work, particularly in relation to time. While further research is needed, we propose that feedback needs to be understood as an interaction between practices, context and individuals.